2022
DOI: 10.1155/2022/3032590
|View full text |Cite
|
Sign up to set email alerts
|

FOXM1 Promotes Drug Resistance in Cervical Cancer Cells by Regulating ABCC5 Gene Transcription

Abstract: Objective. The aim of the present study was to investigate the effect of forkhead box M1 (FOXM1) to paclitaxel resistance in cervical cancer cells, to determine the underlying mechanism, and to identify novel targets for the treatment of paclitaxel-resistant cervical cancer. Methods. Paclitaxel-resistant Caski cells (Caski/Taxol cells) were established by intermittently exposing the Caski cells to gradually increasing concentrations of paclitaxel. The association between FOXM1, ATP-binding cassette subfamily C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Clinically, chemotherapy is the major therapeutic approach for the conventional and essential treatment of cancer patients [3].Several anti-cancer medicines are being used in the clinic as the primary support of the current treatment to reduce the death of cancer patients [15]. However, inherent or acquired resistance to chemotherapeutic drugs (eg, 5-FU, Cisplatin, Paclitaxel and Carboplatin, Doxorubicin, and Tamoxifen) remains the major contributor to therapy failure in solid cancers [15,16,17,18].Theunderlying mechanisms governing the development of chemoresistance are complicated and the leading pathway(s) are ill-de ned.While multiple mechanisms can mediate drug resistance development, FOXM1 is repeatedly identi ed as a common factor associated with weaker response to conventional cancer therapies by regulating several target genes associated with cell cycle and DNA repair [3,5,18,21,22,23,24].There are diverse molecular mechanisms of cancer drug resistance mediated through FOXM1, including enhanced DNA damage repair [23,24,25], oxidative stress prevention [26,27,28], increased drug e ux activity [29,30,31,20], increased thymidylate synthase (TS) activity [32,33], the negative regulation of the JNK/mitochondrial pathway [34], induction of AMPK/mTOR-mediated autophagy [21], orvia up-regulating microtubule dynamics regulation associated components and blocking drug-induced mitotic catastrophe [35,36].Accordingly, the knockdown of FOXM1 or its downstream targets was found very effective in restoring standard chemotherapy sensitivity in many human cancers, including colorectal cancer [20,32], Lung carcinoma [34], breast cancer [36], ovarian cancer [37], prostate cancer…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, chemotherapy is the major therapeutic approach for the conventional and essential treatment of cancer patients [3].Several anti-cancer medicines are being used in the clinic as the primary support of the current treatment to reduce the death of cancer patients [15]. However, inherent or acquired resistance to chemotherapeutic drugs (eg, 5-FU, Cisplatin, Paclitaxel and Carboplatin, Doxorubicin, and Tamoxifen) remains the major contributor to therapy failure in solid cancers [15,16,17,18].Theunderlying mechanisms governing the development of chemoresistance are complicated and the leading pathway(s) are ill-de ned.While multiple mechanisms can mediate drug resistance development, FOXM1 is repeatedly identi ed as a common factor associated with weaker response to conventional cancer therapies by regulating several target genes associated with cell cycle and DNA repair [3,5,18,21,22,23,24].There are diverse molecular mechanisms of cancer drug resistance mediated through FOXM1, including enhanced DNA damage repair [23,24,25], oxidative stress prevention [26,27,28], increased drug e ux activity [29,30,31,20], increased thymidylate synthase (TS) activity [32,33], the negative regulation of the JNK/mitochondrial pathway [34], induction of AMPK/mTOR-mediated autophagy [21], orvia up-regulating microtubule dynamics regulation associated components and blocking drug-induced mitotic catastrophe [35,36].Accordingly, the knockdown of FOXM1 or its downstream targets was found very effective in restoring standard chemotherapy sensitivity in many human cancers, including colorectal cancer [20,32], Lung carcinoma [34], breast cancer [36], ovarian cancer [37], prostate cancer…”
Section: Introductionmentioning
confidence: 99%
“…Considering the importance of ABCC5 in drug resistance, additional studies need to be conducted targeting the role of ABCC5. Scholars demonstrated that ABCC5 is an inducer of MDR in human cancer 39,40) . For instance, ABCC5 could affect pemetrexed resistance in breast cancer 41) .…”
Section: Discussionmentioning
confidence: 99%
“…The FOXM1 transcription factor is crucial for cell proliferation, cell cycle control, cell survival, senescence and DNA damage repair [6,12]. Several studies have indicated that high FOXM1 expression enhances chemotherapy resistance in many cancers, including prostate cancer [20], breast cancer [26], and cervical cancer [14]. FOXM1 reg-ulates many cellular processes, for example, DNA repair, cell survival, drug efflux, and deregulated mitosis [12].…”
Section: Discussionmentioning
confidence: 99%
“…FOXM1 is overexpressed in most human cancers, including the cervix, liver, prostate, breast, etc., which indicates a poor prognosis for cancer patients [8,9]. Furthermore, many researchers have found that FOXM1 is closely associated with cancer drug sensitivity, and downregulation of FOXM1 abrogates drug resistance in different cancer cells [10][11][12], including cervical cancer [13,14]. However, the mechanisms of FOXM1 involvement in chemo-treated cervical cancer remain unclear.…”
Section: Introductionmentioning
confidence: 99%